An assessment model for linking changes in pelagic habitat state to impacts on human wellbeing - Matthew P. Faith; Siân E. Rees; Angus Atkinson; Mike Best; Eileen Bresnan; Michelle J. Devlin; Matthew M. Holland; Holly J. Niner; Clare Ostle; Paul Tett; Abigail McQuatters-Gollop (Marine Policy, 2025)

Mind the gap - The need to integrate novel plankton methods alongside ongoing long-term monitoring - Matthew M. Holland; Luis Felipe Artigas; Angus Atkinson; Mike Best; Eileen Bresnan; Michelle Devlin; Dafne Eerkes-Medrano; Marie Johansen; David G. Johns; Margarita Machairopoulou; Sophie Pitois; James Scott; et al. (Ocean & Coastal Management, 2025)

Predictors of long-term variability in NE Atlantic plankton communities - Matthew M. Holland; Angus Atkinson; Mike Best; Eileen Bresnan; Michelle Devlin; Eric Goberville; Pierre Hélaouët; Margarita Machairopoulou; Matthew Faith; Murray S.A. Thompson; Abigail McQuatters-Gollop (Science of The Total Environment, 2024)

Development of standards for assessing water quality in marine coastal waters of Bahrain - Suzanne J Painting; Andy J. Smith; Ahmed Saeed Khamis; Khalil Hasan Abdulla; William J.F. Le Quesne; Brett P. Lyons; Michelle J. Devlin; Luz Garcia (Marine Pollution Bulletin, 2023)

Major declines in NE Atlantic plankton contrast with more stable populations in the rapidly warming North Sea - Matthew M. Holland; Arnaud Louchart; Luis Felipe Artigas; Clare Ostle; Angus Atkinson; Isabelle Rombouts; Carolyn A. Graves; Michelle Devlin; Birgit Heyden; Margarita Machairopoulou; Eileen Bresnan; Jos Schilder; et al. (Science of The Total Environment, 2023)

Ecosystem-based management of coral reefs from afar – A guide for remote scientists and remote places - Benjamin Cowburn; Khatija Alliji; Joanna K. Bluemel; Elena Couce; Emma Lawrance; Edmund McManus; Nanne van Hoytema; Michelle Devlin (Environmental Science & Policy, 2023)

Coral reefs: The good and not so good news with future bright and dark spots for coral reefs through climate change - Michelle J. Devlin (Global Change Biology, 2022)
COMMENTARY ON Present and future bright and dark spots for coral reefs through climate change. This is a commentary on Sully et al., 2022, https://doi.org/10.1111/gcb.16083

Editorial: Phytoplankton Dynamics Under Climate Change - Elif Eker-Develi; Ahmet E. Kideys; Alexander Mikaelyan; Michelle Jillian Devlin; Alice Newton (Frontiers in Marine Science, 2022)

Editorial: Sustainable Development Goal 14 - Life Below Water: Towards a Sustainable Ocean - Brett W. Molony; Alex T. Ford; Ana M. M. Sequeira; Angel Borja; Anna Milena Zivian; Carol Robinson; Christian Lønborg; Elva G. Escobar-Briones; Emanuele Di Lorenzo; Jesper H. Andersen; Marius N. Müller; Michelle J. Devlin; et al. (Frontiers in Marine Science, 2022)

Sexually Dimorphic Growth Stimulation in a Strain of Growth Hormone Transgenic Coho Salmon (Oncorhynchus kisutch) - Michelle T. T. Chan; Annette Muttray; Dionne Sakhrani; Krista Woodward; Jin-Hyoung Kim; Kris A. Christensen; Ben F. Koop; Robert H. Devlin (Marine Biotechnology, 2021)
Growth hormone (GH) transgenic fish often exhibit remarkable transformations in growth rate and other phenotypes relative to wild-type. The 5750A transgenic coho salmon strain exhibits strong sexually dimorphic growth, with females possessing growth stimulation at a level typical of that seen for both sexes in other strains harbouring the same gene construct (e.g. M77), while males display a modest level of growth stimulation. GH mRNA levels were significantly higher in females than in males of the 5750A strain but equivalent in the M77 strain, indicating sex and transgene insertion locus altered transgene expression. We found that acute estradiol treatments did not influence GH expression in either strain (5750A and M77) or the transgene promoter (metallothionein-B), suggesting that estradiol level was not a significant factor influencing transgene activity. The feminization of XX and XY fish of the 5750A and M77 strains generated all-female groups and resulted in equalized growth of the two genetic sexes, suggesting that the presence of the Y chromosome was not directly capable of influencing the GH transgene–mediated growth in a physiological female conditions. These data suggest that the difference in growth rate seen between the sexes in the 5750A strain arises from non-estradiol-mediated sex influences on gene regulation at the transgene locus. This study shows how genetic factors and transgene insertion sites can influence transgene expression with significant consequent effects on phenotype.

Past and Future Grand Challenges in Marine Ecosystem Ecology - Angel Borja; Jesper H. Andersen; Christos D. Arvanitidis; Alberto Basset; Lene Buhl-Mortensen; Susana Carvalho; Katherine A. Dafforn; Michelle J. Devlin; Elva G. Escobar-Briones; Christian Grenz; Tilmann Harder; Stelios Katsanevakis; et al. (Frontiers in Marine Science, 2020)

Lifeform indicators reveal large‐scale shifts in plankton across the North‐West European shelf - Jacob Bedford; Clare Ostle; David G. Johns; Angus Atkinson; Mike Best; Eileen Bresnan; Margarita Machairopoulou; Carolyn A. Graves; Michelle Devlin; Alex Milligan; Sophie Pitois; Adam Mellor; et al. (Global Change Biology, 2020)
Increasing direct human pressures on the marine environment, coupled with climate‐driven changes, is a concern to marine ecosystems globally. This requires the development and monitoring of ecosystem indicators for effective management and adaptation planning. Plankton lifeforms (broad functional groups) are sensitive indicators of marine environmental change and can provide a simplified view of plankton biodiversity, building an understanding of change in lower trophic levels. Here, we visualize regional‐scale multi‐decadal trends in six key plankton lifeforms as well as their correlative relationships with sea surface temperature (SST). For the first time, we collate trends across multiple disparate surveys, comparing the spatially and temporally extensive Continuous Plankton Recorder (CPR) survey (offshore) with multiple long‐term fixed station‐based time‐series (inshore) from around the UK coastline. These analyses of plankton lifeforms showed profound long‐term changes, which were coherent across large spatial scales. For example, ‘diatom’ and ‘meroplankton’ lifeforms showed strong alignment between surveys and coherent regional‐scale trends, with the 1998–2017 decadal average abundance of meroplankton being 2.3 times that of 1958–1967 for CPR samples in the North Sea. This major, shelf‐wide increase in meroplankton correlated with increasing SSTs, and contrasted with a general decrease in holoplankton (dominated by small copepods), indicating a changing balance of benthic and pelagic fauna. Likewise, inshore‐offshore gradients in dinoflagellate trends, with contemporary increases inshore contrasting with multi‐decadal decreases offshore (approx. 75% lower decadal mean abundance), urgently require the identification of causal mechanisms. Our lifeform approach allows the collation of many different data types and time‐series across the NW European shelf, providing a crucial evidence base for informing ecosystem‐based management, and the development of regional adaptation plans.

Utilizing Eutrophication Assessment Directives From Transitional to Marine Systems in the Thames Estuary and Liverpool Bay, UK - Naomi Greenwood; Michelle J. Devlin; Mike Best; Lenka Fronkova; Carolyn A. Graves; Alex Milligan; Jon Barry; Sonja M. van Leeuwen (Frontiers in Marine Science, 2019)

Seasonal and Temporal Drivers Influencing Phytoplankton Community in Kuwait Marine Waters: Documenting a Changing Landscape in the Gulf - Michelle J. Devlin; Mark Breckels; Carolyn A. Graves; Jon Barry; Elisa Capuzzo; Francisco P. Huerta; Fahad Al Ajmi; Mona M. Al-Hussain; William J. F. LeQuesne; Brett P. Lyons (Frontiers in Marine Science, 2019)

High‐resolution characterization of the abiotic environment and disturbance regimes on the Great Barrier Reef, 1985–2017 - Samuel A. Matthews; Camille Mellin; Aaron MacNeil; Scott F. Heron; William Skirving; Marji Puotinen; Michelle J. Devlin; Morgan Pratchett (Ecology, 2019)
This data compilation synthesizes 36 static environmental and spatial variables, and temporally explicit modeled estimates of three major disturbances to coral cover on the Great Barrier Reef ( GBR ): (1) coral bleaching, (2) tropical cyclones, and (3) outbreaks of the coral‐eating crown‐of‐thorns starfish Acanthaster cf. solaris . Data are provided on a standardized grid (0.01° × 0.01° ~ 1 × 1 km) for reef locations along the GBR , containing 15,928 pixels and excluding the northernmost sections ( GBR reef locations at a fine spatial scale to be used in the development of complex ecosystem models. Static estimates of environmental variables (e.g., depth, bed shear stress, average temperature, temperature variation) originally developed by the Commonwealth of Australia's Environment Research Facility ( CERF ) Marine Biodiversity Hub were provided by Geoscience Australia. Annual (1985–2017) disturbance estimates were either interpolated from empirical data ( A . cf. solaris ), predicted from proxy indicators (e.g., degree heating weeks [ DHW ] as a proxy for bleaching severity), or explicitly modeled (e.g., wave height model for each cyclone). This data set synthesizes some of the most recent advances in remote sensing and modeling of environmental conditions on the GBR ; yet it is not exhaustive and we highlight areas that should be expanded through future research. The characterization of abiotic and disturbance regimes presented here represent an essential tool for the development of complex regional scale models of the GBR ; preventing redundancy between working groups and promoting collaboration, innovation, and consistency. When using the data set, we kindly request that you cite this article and/or the articles cited in the reference section, recognizing the work that went into compiling the data together and the original authors' willingness to make it publicly available.

Optimizing Monitoring Programs: A Case Study Based on the OSPAR Eutrophication Assessment for UK Waters - Luz María García-García; Dave Sivyer; Michelle Devlin; Suzanne Painting; Kate Collingridge; Johan van der Molen (Frontiers in Marine Science, 2019)

Vulnerability of the Great Barrier Reef to climate change and local pressures - Nicholas H. Wolff; Peter J. Mumby; Michelle Devlin; Kenneth R. N. Anthony (Global Change Biology, 2018)
Australia's Great Barrier Reef ( GBR ) is under pressure from a suite of stressors including cyclones, crown‐of‐thorns starfish ( COTS ), nutrients from river run‐off and warming events that drive mass coral bleaching. Two key questions are: how vulnerable will the GBR be to future environmental scenarios, and to what extent can local management actions lower vulnerability in the face of climate change? To address these questions, we use a simple empirical and mechanistic coral model to explore six scenarios that represent plausible combinations of climate change projections (from four Representative Concentration Pathways, RCP s), cyclones and local stressors. Projections (2017–2050) indicate significant potential for coral recovery in the near‐term, relative to current state, followed by climate‐driven decline. Under a scenario of unmitigated emissions ( RCP 8.5) and business‐as‐usual management of local stressors, mean coral cover on the GBR is predicted to recover over the next decade and then rapidly decline to only 3% by year 2050. In contrast, a scenario of strong carbon mitigation ( RCP 2.6) and improved water quality, predicts significant coral recovery over the next two decades, followed by a relatively modest climate‐driven decline that sustained coral cover above 26% by 2050. In an analysis of the impacts of cumulative stressors on coral cover relative to potential coral cover in the absence of such impacts, we found that GBR ‐wide reef performance will decline 27%–74% depending on the scenario. Up to 66% of performance loss is attributable to local stressors. The potential for management to reduce vulnerability, measured here as the mean number of years coral cover can be kept above 30%, is spatially variable. Management strategies that alleviate cumulative impacts have the potential to reduce the vulnerability of some midshelf reefs in the central GBR by 83%, but only if combined with strong mitigation of carbon emissions.

Effect of growth hormone overexpression on gastric evacuation rate in coho salmon - Jin-Hyoung Kim; Satid Chatchaiphan; Michelle T. Crown; Samantha L. White; Robert H. Devlin (Fish Physiology and Biochemistry, 2018)

A Review of the Tools Used for Marine Monitoring in the UK: Combining Historic and Contemporary Methods with Modeling and Socioeconomics to Fulfill Legislative Needs and Scientific Ambitions - Tim P. Bean; Naomi Greenwood; Rachel Beckett; Lauren Biermann; John P. Bignell; Jan L. Brant; Gordon H. Copp; Michelle J. Devlin; Stephen Dye; Stephen W. Feist; Liam Fernand; Dean Foden; et al. (Frontiers in Marine Science, 2017)

Identification of SNPs associated with transgenic and sex phenotypes in coho salmon (Oncorhynchus kisutch) - Erin McClelland; Michelle Chan; Dionne Sakhrani; Robert Devlin (Conservation Genetics Resources, 2016)

Effects of reduced water quality on coral reefs in and out of no‐take marine reserves - Amelia S. Wenger; David H. Williamson; Eduardo T. da Silva; Daniela M. Ceccarelli; Nicola K. Browne; Caroline Petus; Michelle J. Devlin (Conservation Biology, 2016)
Near‐shore marine environments are increasingly subjected to reduced water quality, and their ability to withstand it is critical to their persistence. The potential role marine reserves may play in mitigating the effects of reduced water quality has received little attention. We investigated the spatial and temporal variability in live coral and macro‐algal cover and water quality during moderate and major flooding events of the Fitzroy River within the Keppel Bay region of the Great Barrier Reef Marine Park from 2007 to 2013. We used 7 years of remote sensing data on water quality and data from long‐term monitoring of coral reefs to quantify exposure of coral reefs to flood plumes. We used a distance linear model to partition the contribution of abiotic and biotic factors, including zoning, as drivers of the observed changes in coral and macro‐algae cover. Moderate flood plumes from 2007 to 2009 did not affect coral cover on reefs in the Keppel Islands, suggesting the reef has intrinsic resistance against short‐term exposure to reduced water quality. However, from 2009 to 2013, live coral cover declined by ∼50% following several weeks of exposure to turbid, low salinity water from major flood plume events in 2011 and subsequent moderate events in 2012 and 2013. Although the flooding events in 2012 and 2013 were smaller than the flooding events between 2007 to 2009, the ability of the reefs to withstand these moderate floods was lost, as evidenced by a ∼20% decline in coral cover between 2011 to 2013. Although zoning (no‐take reserve or fished) was identified a significant driver of coral cover, we recorded consistently lower coral cover on reserve reefs than on fished reefs throughout the study period and significantly lower cover in 2011. Our findings suggest that even reefs with an inherent resistance to reduced water quality are not able to withstand repeated disturbance events. The limitations of reserves in mitigating the effects of reduced water quality on near‐shore coral reefs underscores the importance of integrated management approaches that combine effective land‐based management with networks of no‐take reserves.

Extending the phytoplankton tool kit for the UK Water Framework Directive: indicators of phytoplankton community structure - Michelle Devlin; Jon Barry; Suzanne Painting; Mike Best (Hydrobiologia, 2009)